2018
DOI: 10.1016/j.ekir.2018.08.006
|View full text |Cite|
|
Sign up to set email alerts
|

Proenkephalin A 119-159 (Penkid) Is an Early Biomarker of Septic Acute Kidney Injury: The Kidney in Sepsis and Septic Shock (Kid-SSS) Study

Abstract: IntroductionSepsis is the leading cause of acute kidney injury (AKI) in critically ill patients. The Kidney in Sepsis and Septic Shock (Kid-SSS) study evaluated the value of proenkephalin A 119-159 (penkid)—a sensitive biomarker of glomerular function, drawn within 24 hours upon intensive care unit (ICU) admission and analyzed using a chemiluminescence immunoassay—for kidney events in sepsis and septic shock.MethodsThe Kid-SSS study was a substudy of Adrenomedullin and Outcome in Severe Sepsis and Septic Shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 29 publications
8
70
0
3
Order By: Relevance
“…On the other hand, a high value of penKid seems to represent a more important state of risk than a low value of eGFR, as penKid predicted 28-day mortality, whereas eGFR did not. This is in line with several previous studies (11,(15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, a high value of penKid seems to represent a more important state of risk than a low value of eGFR, as penKid predicted 28-day mortality, whereas eGFR did not. This is in line with several previous studies (11,(15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
“…Similar rates of AKI incidence and mortality are presented in a recent study on septic AKI in the unselected ED setting(11), while others have shown slightly higher rates of mortality and AKI in recent publications, but these studies were carried out in the critical care setting, studying patients after ICU-admission. (15,16) The current definition of AKI, both with and without presence of sepsis, is based on the KDIGO-or RIFLE-criteria, which include SCr and urine output. These markers have been mainstays in previous iterations of septic AKI definitions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in healthy and diseased adults supports PENK as an early indicator of AKI and independent predictor of impaired kidney function. Moreover, PENK was strongly correlated with estimated and measured GFR after cardiac surgery and in septic patients [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 86%